Similar levels of disease activity and remission rates in patients with psoriatic arthritis and rheumatoid arthritis-results from the Finnish quality register - Weman, Lauri (Springer Nature, 2025)
Objectives
To compare the current disease activity and remission rates, and their regional variation in patients with psoriatic arthritis (PsA) and rheumatoid arthritis (RA) in Finland.
Methods
Data of patients’ most recent visit in 1/2020–9/2021 were extracted from the Finnish Rheumatology Quality Register. Measures for disease activity and remission included joint counts, DAS28, cDAPSA, CDAI, the Boolean definition, and physician assessment. Regression analyses were applied, adjusted for age and sex.
Results
Data of 3598 patients with PsA (51% female, mean age 54 years) and 13,913 patients with RA (72% female, 74% ACPA-positive, mean age 62 years) were included. The median (IQR) DAS28 was 1.9 (1.4, 2.6) in PsA and 2.0 (1.6, 2.7) in RA (p = 0.94); for cDAPSA, the median (IQR) values were 7.7 (3.1, 14) in PsA and 7.7 (3.3, 14) in RA (p < 0.001). In all regions in both diseases, the median DAS28 was ≤ 2.6 and the median cDAPSA < 13. Remission rates included DAS28 < 2.6 in 73% in PsA and 69% in RA (p = 0.17) and Boolean remission in 17% in PsA and 15% in RA (p < 0.001). By other definitions of remission, the rates ranged between 30% and 46%. Methotrexate was currently used by 49% in PsA and 57% in RA (p < 0.001). Self-administered bDMARDs were currently used by 37% in PsA and 21% in RA (p < 0.001).
Conclusion
The overall disease activity was low and similar in patients with PsA and RA across the country. Remission rates varied between 15 and 73%, depending on the definition but were similar in PsA and RA.